ANALISIS RISIKO KONSTRUKSI PADA PEKERJAAN PEMBANGUNAN SUTET 500 KV BALARAJA -KEMBANGAN - Bayu Nugroho; Eri Setia Romadhon; Muhammad Nafhan Isfahani (FTSP Universitas Jayabaya, 2022)
The construction of the 500 kV Balaraja - Kembangan SUTET consisting of 157 towers with a channel length of 47.2 km route has a large enough risk that it can cause delays and even failure.The long path and substantial social problems resulted in many negative impacts on its implementation. For this reason, the risks may need to be analyzed so that the project can proceedas planned. This final project aims to identify the risks of implementing the 500 kV SUTET Balaraja- Kembangan development project, analyze the dominant risks and determine the risk response ofthemost dominant risks. The research process was carried out by conducting surveys, distributingquestionnaires, and interviews. The series of analyzes begins with risk identification through aliterature study. After that, a risk analysis is carried out by distributing questionnaires to previouslyselected respondents.Risk analysis is carried out by estimating the most significant possible risk and the resulting impacton time and cost. The final step is to determine the risk response to this project by interviewing competent parties. Based on the analysis results, it is known that the dominant risk variable concerning time is challenging to site location conditions. In contrast, the most dominant risk to cost is poor contractor performance.